On the Presence and Thermalization of Cold Ions in the Exhaust of Antiparallel Symmetric Reconnection - Norgren , Cecilia; Tenfjord , Paul; Hesse , Michael; Toledo-Redondo , Sergio; Li , Wen-Ya; Xu , Yin; Kwagala , Norah Kaggwa; Spinnangr , Susanne; Kolstø , Håkon; Moretto , Therese (Frontiers in Astronomy and Space Sciences, 2021)
Using fully kinetic 2.5 dimensional particle-in-cell simulations of anti-parallel symmetric magnetic reconnection, we investigate how initially cold ions are captured by the reconnection process, and how they evolve and behave in the exhaust. We find that initially cold ions can remain cold deep inside the exhaust. Cold ions that enter the exhaust downstream of active separatrices, closer to the dipolarization front, appear as cold counter-streaming beams behind the front. In the off-equatorial region, these cold ions generate ion-acoustic waves that aid in the thermalization both of the incoming and outgoing populations. Closest to the front, due to the stronger magnetization, the ions can remain relatively cold during the neutral plane crossing. In the intermediate exhaust, the weaker magnetization leads to enhanced pitch angle scattering and reflection. Cold ions that enter the exhaust closer to the X line, at active separatrices, evolve into a thermalized exhaust. Here, the cold populations are heated through a combination of thermalization at the separatrices and pitch angle scattering in the curved magnetic field around the neutral plane. Depending on where the ions enter the exhaust, and how long time they have spent there, they are accelerated to different energies. The superposition of separately thermalized ion populations that have been accelerated to different energies form the hot exhaust population.